Suddenly, last summer - Williams, Tennessee 1911-1983; Arnold, Malcolm 1921-2006; Orr, Buxton 1924-1997 (Powerhouse films, 2020)
"Das kunstvoll gebaute Dialogstück von Tennessee Williams in glänzend gespielter und psychologisch glaubwürdiger Filmfassung: Die Reisebegleiterin eines verwöhnten Dichters muß mit ansehen, wie der psychisch labile junge Mann unter schauerlichen Umständen getötet wird. Dank der Hilfe eines Nervenarztes gelingt es ihr, die Wahrheit auszusprechen und das Erlebte zu bewältigen." [filmdienst.de]
Original: Großbritannien, USA 1959
Indicator Blu-Ray edition special features: 4K restoration from the original negative ; original mono audio ; "Joseph L Mankiewicz Interview" (1990, 10 mins): the renowned filmmaker discusses his career in a segment from the French TV series Cinéma cinémas ; "Elizabeth Taylor on Montgomery Clift" (1966, 2 mins): the celebrated actress pays tribute to her friend and co-star shortly after his tragic death in July 1966 ; "Gary Raymond on 'Suddenly, last summer'" (2018): a new interview with the versatile British actor ; "About last summer" (2018, 16 mins): second assistant editor John Crome shares his experience of making "Suddenly, last summer ; "Remembering last summer" (2018, 3 mins): continuity supervisor Elaine Schreyeck recalls working with Mankiewicz, Hepburn and Clift ; "The predator and the prey" (2017, 26 mins): critic and film historian Michel Ciment examines the film's production and explores its complex themes and concerns ; isolated music and effects track ; original theatrical trailer ; trailer commentary with Dan Ireland (2013, 3 mins): a short critical appreciation ; image gallery: on-set photography, publicity stills and promotional materials ; new and improved English subtitles for the deaf and hard-of-hearing
Keywords: Film; Blu-Ray-Disc